New creative perspective on existential and social undercurrents in British Gothic novels - Nair, Aswathy A. S.; Dwivedi, Laxmi Dhar (Creativity Studies, 2024)
Changes that occur often in the world around us in accordance with each period’s change. It is a common trend in writing to introduce new tendencies, and the Gothic subgenre exhibits this tendency. The term Gothic has its roots in the early 16th century and refers to a mysterious quality that appears in some metaphysical items. This paper is a humble attempt to explore the history of the Gothic novel and demonstrate how mystery alone recreates this genre in British literature. The ability of intangible components to incite fear in readers was lessened with the rise of the mysterious portrayal of a story in day-to-day life. As the Gothic novel began to examine reality, readers’ desire to learn the truth increased. This paper investigates to understand the reasons for the abrupt disappearance of metaphysical components and increased focus and importance on existential and social issues by examining a few randomly chosen modern novels and comparing them to the earlier Gothic classics. It highlights the differences occurring in readers’ views according to the various times while also evaluating the variance occurring within the Gothic genre.